Transformation of Islamic Islamic Preaching in the Digital Era: a Comparative Study of the Salaf Al-Basyariyah Islamic Boarding School in Madiun and the Modern Islamic Boarding School in Nurul Jadid in Probolinggo - Luthfi Ulfa Ni’amah; Clara Sinta Pratiwi (DAWUH : Islamic Communication Journal, 2026)
This study explores the transformation of Islamic boarding school da'wah in the digital era implemented by two types of Islamic boarding schools, namely Al-Basyariyah Islamic boarding school in Madiun as a representative of Salaf Islamic boarding schools and Nurul Jadid Islamic boarding school in Probolinggo as a representative of modern Islamic boarding schools. Al-Basyariyah Islamic boarding school, despite having limited facilities and a simple team, has still begun to adapt to social media as a medium for da'wah, especially in sharing daily activities. Likewise, Nurul Jadid Islamic boarding school utilizes complete equipment and a structured content management team, with a focus on informative posts about Islamic da'wah. The results of the study show that the transformation of Islamic boarding school da'wah in the digital era is carried out through digital activism through social media such as websites, Facebook, Instagram, TikTok, and YouTube. The impacts resulting from digital activism as a form of da'wah transformation in the digital era are expanding the reach of da'wah, creating a positive image of Islamic boarding schools because they can conduct da'wah that is relevant to current developments, and can shape students who have skills in the field of multimedia.